EFFECT OF COUNSELING FOR CONSTIPATION IN PRIMARY SCHOOL CHILDREN: A SURVEY STUDY - Borkar, *Kanchan M; V Shekokar, Anantkumar (International Journal of Ayurveda and Pharma Research, 2017)
Constipation is a very common problem which affects large number of school going population of children. The most of the gastroenterologist, pediatricians and proctologist encounter with this problem routinely. Socio-economic factors play significant role towards the prevalence of disease. The dietary habits & life style pattern also leads constipation in children. This article presented a survey study based on primary school children suffered with constipation. The study revealed causes of constipation mainly associated with social & daily routine activities. The 83% of affected students were found to have bad dietary habits. The 56 % of affected children were found to possess lack of outdoor sports activity. Counseling to students, teachers and parents help to change their diet pattern and living habits in natural way. The present study also suggests guideline or rules to be adopted for curing problem of constipation in primary school children.